2022
DOI: 10.1002/adts.202200178
|View full text |Cite
|
Sign up to set email alerts
|

Spin‐Transport through Van der Waals Heterojunctions Based on 2D‐Ferromagnet and Transition Metal Dichalcogenides: A Study from First‐Principles Calculations

Abstract: Recently reported 2D ferromagnets show tremendous potential for their application in low‐dimensional spintronic devices. Semiconductor heterostructure consisting of 2D ferromagnet integrated with other suitable 2D semiconducting materials may pave the way for designing robust and sophisticated spin‐transport devices within a few nanometer scales. In this regard, a detailed understanding of the interface properties of 2D ferromagnetic materials and other 2D semiconductors is highly essential. Herein, the interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The figure of merit (defined as TMR) of the systems is evaluated as the resistance difference between adjacent parallel and anti-parallel states of ferromagnets. Several studies have reported high TMR values for graphite/CrI 3 /graphite junctions [34,[156][157][158]. Large TMR is observed at low temperatures and at higher bias voltage [34], which is opposite in nature than the conventional magnetic tunnel junctions.…”
Section: Application In Spintronic Devices and Other Possible Applica...mentioning
confidence: 98%
“…The figure of merit (defined as TMR) of the systems is evaluated as the resistance difference between adjacent parallel and anti-parallel states of ferromagnets. Several studies have reported high TMR values for graphite/CrI 3 /graphite junctions [34,[156][157][158]. Large TMR is observed at low temperatures and at higher bias voltage [34], which is opposite in nature than the conventional magnetic tunnel junctions.…”
Section: Application In Spintronic Devices and Other Possible Applica...mentioning
confidence: 98%